Gillespie Algorithms for Stochastic Multiagent Dynamics in Populations and Networks - Masuda, Naoki (Elements in the Structure and Dynamics of Complex Networks, 2022)
This Element provides a tutorial on the Gillespie algorithms focusing on social multiagent dynamics and also review their recent extensions. The first main part focuses on simulation of social multiagent dynamics occurring in populations and networks, and the remainder reviews recent extensions of the Gillespie algorithms.